Human Factors Design of Digital Information Systems for Inspection Body (IB) in Industry 4.0 Era - Jongprasithporn, Manutchanok; Yodpijit, Nantakrit; Tontoh, Danitar; Sittiwanchai, Teppakorn (My University, 2020)
Industry 4.0 highly considers new industrial products and services platforms where various emerging technologies are combining to implement for digital solutions. Digital transformation plays a significant role in the disruption of the traditional information systems and drives the business to digitalization. The Inspection Body (IB) conducts technical assessments, generally by providing factory/business inspection services on behalf of private customers or their parent organizations to provide them with industrial product certification and/or information on compliance with legislation, standards, specifications, and contractual commitments. Importantly, data accuracy, traceability, and confidentiality controls are critical for IB operations where the digital information systems can significantly enhance the planning, managing, and monitoring of the IB’s Management Information System (MIS). This paper presents both theoretical and practical applications of human factors product design and development to make a useful and easy to use digital information systems for IB. Major methods for human factors design includes the focus of potential users, the empirical measurement of usage, and the iterative design where the simulated, prototype, and real models are created. Limitations and future work for human factors design for digital information systems in other industrial businesses are also discussed.
Keywords: Digital information systems; Human factors design; Inspection Body (IB); Management Information System (MIS)